Solve this system algebraically.
9x + 2y = 5
y - 2x + 3 = 0

Question

Asked 3/19/2013 9:27:03 AM

Updated 242 days ago|11/18/2017 3:41:04 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by Masamune [11/18/2017 3:40:47 AM]

shifa saleheen|Points 9966|

Question

Asked 3/19/2013 9:27:03 AM

Updated 242 days ago|11/18/2017 3:41:04 AM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by Masamune [11/18/2017 3:40:47 AM]

Rating

3

9x + 2y = 5

y - 2x + 3 = 0

y = 2x - 3

9x + 2(2x - 3) = 5

9x + 4x - 6 = 5

13x - 6 = 5

13x = 5 + 6

13x = 11

x = 11/13

y - 2(11/13) + 3 = 0

y - 22/13 + 3 = 0

y + 17/13 = 0

y = -17/13/

Solution set:**(11/13, -17/13)**

y - 2x + 3 = 0

y = 2x - 3

9x + 2(2x - 3) = 5

9x + 4x - 6 = 5

13x - 6 = 5

13x = 5 + 6

13x = 11

x = 11/13

y - 2(11/13) + 3 = 0

y - 22/13 + 3 = 0

y + 17/13 = 0

y = -17/13/

Solution set:

Added 242 days ago|11/18/2017 3:41:04 AM

This answer has been confirmed as correct and helpful.

27,094,575

questions answered

There are no comments.